Pengaruh Latar Belakang Pendidikan dan Kompetensi Terhadap Kualitas Laporan Keuangan di Lingkungan ASN Kabupaten Jepara - Prita Riani Atifa Rana; Annas Rahmat Ramadhani (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
Financial statements are valuable tools for decision making as they detail an entity’s financial condition and growth over a specific period of time. A number of factors, such as the education levell and experience of the accuracy and reliability of financial statements. This research aims to examine the influence of educational background and competence on the quality of financial statements in the context of Civil Servants (ASN) in Jepara Regency. This study employs a quantitative methodology, focusing on Civil Servants, including treasurers and accounting personnel in Jepara Regency. The researcher collected data from 70 respondents using data collection instruments. Instrument validity was assessed using the R-value (corrected item-total correlation) for each item, and reliability was evaluated using Cronbach’s Alpha. Using linear regression, (T and F) tests and determination coefficients to test the hypothesis. The researcher’s findings show that educational background has a superior impact on the quality aspect of financial reports. Competence plays a strong role in the quality of financial reports. However, together, these variables contribute significantly to the level of quality of financial reports in the context of the State Civil Apparatus (ASN) of Jepara Regency.